(untitled) (Universal International Scientific Journal, 2026)
. The study of the chemical composition of the essential oil of Ferula Sumbul is of great importance for the standardization of essential oils, assessment of pharmacological activity and classification of biochemical properties of raw materials. In this work, Ferula Sumbul essential oil was analyzed using the GC–MS method, and chemotype (phenotype) characteristics were determined based on its chemical composition. As a result of the analysis, 49 components were identified in the essential oil, and the main components were 1S-α-pinene (23.36%), β-pinene (20.60%), (E)-longipinene (12.48%), β-myrcene (7.67%) and cis-sabinene (5.23%). The results obtained showed that Ferula Sumbul essential oil belongs to the α-pinene–β-pinene dominant monoterpene chemotype.